Penggunaan Tepung Limbah Organik Pasar Sebagai Pengganti Dedak dalam Ransum Ternak Itik Petelur - Bachtar Bakrie; Umming Sente; Dini Andayani (Jurnal Penelitian Pertanian Terapan, 2011)
Organic waste materials such as flour market (TLOP) have the potential to be used as a substitute for rice bran in poultry rations. This study aims to determine the level of efficiency and effectiveness TLOP in the ration on production of laying ducks levels and quality of duck eggs. The experiment was conducted using Completely Randomized Design with four treatment and 38 replicates each. This type of treatment is replacement of rice bran in the ration with TLOP as: a) 0% (P-0), b) 10% (P-10), c) 20% (P-20) and 30% (P-30). Used 160 ducks consisting of 152 females ducks and 8 males were placed in 8 cages and each filled in 20 ducks were 19 females and 1 male ducks. Observations made during three months and the observed parameters are included the percentage of the daily egg production and egg quality. The results showed that the highest daily production of eggs contained in the treatment of P-30 (average 80.5%), but not significantly different (P>0.05) with P-0 (79.1%) and P-20 (77, 1%) but significantly different (P<0.05) with P-10 (75.2%). Observation of the quality of the eggs they did not look real difference, except in the quality Haught Unit (HU) and egg yolk color index. Haught Unit (HU) increase from 87 to 92, while egg yolk color index change from 14** to 14***. Concluded that TLOP can be used as a substitute for bran feed material up to 30% in the rations of laying ducks Keywords: Organic waste materials, Bran, laying Ducks, egg production, egg quality